Stability and Bifurcation of a Prey-Predator-Scavenger Model in the Existence of Toxicant and Harvesting - Huda Abdul Satar; Raid Kamel Naji (International Journal of Mathematics and Mathematical Sciences)
In this paper a prey-predator-scavenger food web model is proposed and studied. It is assumed that the model considered the effect of harvesting and all the species are infected by some toxicants released by some other species. The stability analysis of all possible equilibrium points is discussed. The persistence conditions of the system are established. The occurrence of local bifurcation around the equilibrium points is investigated. Numerical simulation is used and the obtained solution curves are drawn to illustrate the results of the model. Finally, the nonexistence of periodic dynamics is discussed analytically as well as numerically.